Emotive Interjections of Admiration in Acehnese: A Study of Natural Semantics - Taib, Rostina; Muyadi, Muyadi; Muskar, Rahlina; Syarfina, T. (Proceeding International Conference on Malay Identity, 2024)
This study aims to identify, classify, and analyze emotive interjections expressing 'admiration' in the Acehnese language using the Natural Semantic Metalanguage (NSM) approach. The method applied is descriptive qualitative with verbal data containing interjections. The research data source was obtained from the daily conversations of the Acehnese people in four regions, namely Aceh Besar, North Aceh, East Aceh, and West-South Aceh. Each region was represented by 3 informants who met the criteria, such as speaking Acehnese as their mother tongue, aged between 30 and 50 years, and were willing to become informants. The techniques of collecting the data include observation, recording and recording. Data analysis was carried out in several steps, namely data identification and inventory, classification and data analysis based on categories and meaning of emotive interjections. The research results show that emotive interjections in Acehnese include alahuwe, ômmi, ômma, ômman, ômmen, ômma ôi, bak budik, bak budôk, alah mak ôi, lahwa ôi, ie eh ek, ek, ôku, ôdu, and bah. These interjections can be grouped into several emotive subcategories based on their semantic components: 1) 'I feel that something good has happened,' 2) 'I feel that something good will happen,' and 3) 'I feel that something like this is impossible.' Each subcategory has specific meaning characteristics and usage within the cultural and linguistic context of Aceh. This research contributes significantly to a more comprehensive understanding of the Acehnese language, particularly regarding the semantics of emotive interjections, and may serve as a foundation for further studies on interjections in other regional languages in Indonesia.